An interactive educational program to develop innovative imagination among students Institute of Fine Arts in Pictorial Creation (Journal of the College of Basic Education, 2025)
This research aims to develop an interactive educational program based on the Processes of Complex Thinking Model (Presseisen) to enhance innovative imagination among third-year students in the Pictorial Composition course at the Institute of Fine Arts. This initiative responds to the urgent need for improving teaching methods in a way that aligns with the learners’ characteristics and the specific nature of the artistic subject. The educational program is conceived as an integrated system designed to achieve specific learning objectives through flexible, organized stages.The program involved several essential steps, including defining general and specific objectives, preparing appropriate educational content, selecting suitable activities and teaching tools, and designing evaluation instruments to measure its effectiveness. The program was applied to a sample of 22 students from the Fine Arts Institute for Boys – Department of Fine Arts, who were randomly divided into two groups: an experimental group and a control group (11 students in each), ensuring equivalence in key variables such as age, academic achievement, and intelligence.The researcher employed a quasi-experimental design with pre- and post-testing. She also developed a skill-based and cognitive test, along with a scale to measure innovative imagination. The results revealed the superiority of the experimental group, indicating the effectiveness of the program in enhancing students’ understanding, application skills, and imaginative abilities. The thesis consists of four chapters: the first addresses the research problem, its significance, objectives, and hypotheses; the second provides a theoretical framework discussing the program, innovative imagination, and pictorial composition; the third presents the research methodology; and the fourth includes the results, conclusions, recommendations, and suggestions. The researcher concludes with several recommendations advocating for the use of scientifically grounded educational programs in teaching pictorial composition, aiming to foster students’ creativity and broaden their artistic imagination.